Maternal Anxiety: presence of risk to child development and retest of newborn hearing screenin - Fernanda Donato Mahl; Eliara Pinto Vieira Biaggio; Themis Maria Kessler (O Mundo da Saúde)
This study aimed to examine possible associations between risk to child development and maternal anxious state, as well as the association between maternal anxiety and knowledge about the retest in the Newborn Hearing Screening (NHS). 85 mothers were interviewed who came to the NHS Programme for audiological retest of their babies, because they had failed in the NHS first and had initial suspicion of hearing impairment. It was carried out an interview with the mothers using a questionnaire aiming to evaluate their knowledge about the retest on the NHS. Then, to investigate the level of maternal anxiety before performing the retest on the NHS for their children the Beck Anxiety Inventory was applied. Finally, we observed and analyzed the Indicators of Risk for Child Development – IRDIs to evaluate the interaction between mother and baby. The results of this research demonstrated that maternal anxiety correlates directly to the Indicators of Risk for Child Development, in other words, in the case of presence of maternal anxiety we observed the absence of IRDIs 1, 2, 4 and 5. In relation to the knowledge about the retest of the NHS, it was observed that there exists a significant association between the level of anxiety of mothers and knowledge absence about retest of the NHS, because 86.8% of mothers who did not know what the retest is were anxious. We conclude that there was a positive association between the presence of risk to child development and maternal emotional state of anxiety. Also, there was a predominance of anxiety in mothers who did not know what is to retest the NHS.